Apical Hypertrophic Cardiomyopathy and Multiple Coronary Artery-Left Ventricular Fistulas: A Case Report. - Massimo, Ruggiero; Francesco, Tota; Marco, Sassara; Nicola, Locuratolo; Vito, Calvani; Ilaria, Dentamaro; Maria, Tesorio; Pietro, Scicchitano; Pasquale, Caldarola; Marco, Matteo Ciccone (Journal of Hypertension and Cardiology, 2013)
We describe a rare case of multiple coronary artery-left ventricular fistulas associated with apical hypertrophic cardiomyopathy in a 62 year asymptomatic old male admitted to our department for a perioperative evaluation of non cardiac surgery, already diagnosed for multiple coronary artery-left fistulae. He underwent transthoracic echocardiography and then to accelerated dipiridamole stress-echo.
Keywords: coronary artery left-ventricular fistulae; apical hypertrophic cardiomyopathy; echocardiography.